Reich - Rycroft. Charles (London, 1979)
Although this is no a biography of Reich, some of his life have to be mentioned id we are to understand his ideas and place them correct in history. Reich was born on March 24th 1897 at Dobrzynica in Galicia but spent most of his childhood on a farm at Jujinetz in Bukowina. Both Galicia and Bukowina were outlaying provinces of the Austro-Hungarian Empire until its collapse at the end of the First World War, and Reich was therefore an Austrian citizen but one whose home country was abroad.
Keywords: Reich